Endogenous Growth in an Open Economy and the Real Exchange Rate - Daniela Federici; Giancarlo Gandolfo (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper is a step in the direction of a larger research project aimed at determining the long run equilibrium value of the euro/dollar real exchange rate. Given this value, one could then give a precise meaning to the notion of undervaluation or overvaluation of the euro, and calculate its misalignment. The problem however arises of how to assess the reliability of such misalignment calculations. In our opinion, we must have a benchmark (namely a period in which we exactly know from outside sources the misalignment itself), against which we can test the validity of the model underlying our calculations. This of course is not (yet) possible for the euro, so that all the calculations of the misalignment of the euro that have been made can only be compared with one another, without knowing which is the good one. Hence, before building a model to be applied to the euro/dollar, we tested our ideas incorporating them in a basic model to be applied to the lira/dollar in a period in which we do exactly know the actual misalignment of the lira from outside sources.
Keywords: 330; NATREX; equilibrium exchange rates; international capital flows; misalignment